Risk of perforation in balloon dilation associated with steroid injection for preventing esophageal stricture after endoscopic submucosal dissection - Tsujii, Yoshiki; Hayashi, Yoshito; Kawai, Naoki; Yamada, Takuya; Yamamoto, Katsumi; Hayashi, Shiro; Yoshii, Shunsuke; Nagai, Kengo; Inoue, Takuya; Nishida, Tsutomu; Iijima, Hideki; Mita, Eiji; Inoue, Atsuo; Takehara, Tetsuo (Endoscopy International Open, 2017)
Background and study aims Endoscopic local steroid injection (LSI) has been used to prevent esophageal strictures after endoscopic submucosal dissection (ESD) for superficial esophageal neoplasms (SENs). This study aimed to evaluate the safety and efficacy of LSI therapy.Patients and methods From May 2007 to September 2014, at four institutions, 40 consecutive patients with SENs were treated with ESD that left a mucosal defect of more than three-quarters of the esophageal circumference. Two patients who underwent esophagectomy after ESD were excluded, and 38 patients were analyzed. The incidence of post-ESD strictures and adverse events associated with LSI were retrospectively investigated.Results Prophylactic LSI was administered in 28 patients (LSI group), and not administered in 10 patients (Non-prevention group). Post-ESD stricture rates were significantly lower in the LSI group (43 %) than in the Non-prevention group (90 %) (P = 0.012). Endoscopic balloon dilation (EBD) was conducted in 11 patients (39 %) in the LSI group and in 7 (70 %) in the Non-prevention group. In the LSI group, perforation caused by EBD occurred in five patients, while in the Non-prevention group, it occurred in only one patient who had received subsequent LSI before the perforation. Four patients with perforation successfully recovered after conservative therapy, but the other two patients required surgical treatment. A review of follow-up examinations with endoscopic ultrasonography and narrow-band imaging showed impaired ulcer-healing process after LSI.Conclusion LSI is useful for preventing post-ESD strictures, but it appears to increase the risk of perforation in cases of EBD.